Sequential villages and settling down on the southeast U.S. coast - Cajigas, Rachel; Sanger, Matthew C.; Semon, Anna M.; Thompson, Victor D.; Garland, Carey J.; Blair, Elliot H.; Thomas, David Hurst (Frontiers in Human Dynamics, 2024)
The adoption of more sedentary residential practices is a long process in which groups shift in size, permanence, makeup, and even location in response to the social, demographic, ecological, and subsistence pressures associated with settling down. Coastal peoples living in the Southeast U.S. are among the first to adopt more sedentary lifeways in North America as evidenced by their creation of dozens of large circular or arcing shell middens during the end of the Middle Holocene and start of the Late Holocene. Relying on material culture studies and AMS radiocarbon data refined using Bayesian statistical modeling, we investigate the sequential establishment and abandonment of three village sites built over more than 300 years and located only a few kilometers apart. These studies reveal important insights into the process of adopting more sedentary practices in the region and how local communities adapted to associated pressures.